From a research study to a conservation partnership: Developing approaches to restoring common scoter populations. Issue 9 (18th September 2020) - Hancock, Mark H.; Robson, Hannah J.; Smith, Trevor D.; Stephen, Alastair; Byrne, Paul; MacLennan, Alison; Klein, Daniela; Mitchell, Carl; Griffin, Larry R.; Hilton, Geoff; Dobson, Henry; Douse, Andy
Abstract: 1. Like many sea‐duck populations, the British breeding population of common scoters Melanitta nigra has declined markedly. In 2009, a study was established to measure factors affecting lake use by breeding scoters, to inform conservation measures. That study, published in Aquatic Conservation: Marine and Freshwater Ecosystems (AQC) in 2016, showed that lakes used by scoters had relatively more shallow water and large invertebrates. Furthermore, lakes with abundant large invertebrates had relatively few brown trout Salmo trutta . These results probably reflect the importance of foraging habitat (shallow water), prey abundance (large invertebrates), and competition for prey (trout abundance) in influencing scoter lake use. 2. To develop this study, additional research, and scoter conservation measures, we formed a long‐term partnership, comprising nature conservation non‐governmental organizations, statutory agencies, fisheries managers and the regional hydropower company. The partnership meets regularly to coordinate and review research and develop conservation measures, building on the earlier lake‐use study. 3. At key scoter lakes managed for hydropower, the partnership negotiated a revised water level management regime, favouring shallow water availability in the breeding season. This regime was informed by additional research, showing the value of certain islands for nesting scoters, and water level requirements to maintain these as islands. 4. In a different key scoter area — an extensive near‐natural peatland where recreational angling takes place — the partnership established a trial of increased brown trout angling, with increased fish removal, to determine whether this would increase invertebrate prey abundance and benefit breeding scoters. Both conservation interventions are currently being evaluated by detailed monitoring. 5. Overall, the earlier study published in AQC, was important in strengthening and informing our researcher–practitioner partnership, as we collaborated within an adaptive management framework to reverse scoter declines. Long‐term interdisciplinary partnerships are likely to have an important role to play in general, for the successful conservation of aquatic biodiversity.